Effects of skills training on employment and livelihood outcomes: A randomized controlled trial with young women in Ghana - Sarah Frohnweiler; Charles A. Adongo; Bernd Beber; Tabea Lakemann; Jan Priebe; Jann Lay (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
We use a randomized controlled trial to examine the short- and mid-term impacts of a best-practice training program on (non-)employment outcomes in Ghana. Overall the program did not affect core labor market outcomes at the extensive (employment) and intensive (hours of work, income) margin, but it (i) induced occupational sorting, with treated individuals more likely to work in their field of specialization, (ii) partially improved job quality (written contracts, medical benefits), and (iii) led to better outcomes on a variety of non-labor market indicators (mental health, delayed marriages, access to finance). We also explore policy stakeholders' expectations and perceptions of program success. We find that stakeholders (i) have overly optimistic prior beliefs about the program's impact on core outcomes and (ii) do not update their beliefs as we would expect from Bayes' rule when presented with information about the program's circumscribed effectiveness. We speculate that this result suggests an obstacle for adaptive programming in development cooperation and could help explain the persistence of some suboptimal labor market interventions. – – Anhand einer randomisierten kontrollierten Studie untersuchen wir die kurz- und mittelfristigen Auswirkungen eines Best-Practice-Ausbildungsprogramms auf Beschäftigung und Lebensbedingungen in Ghana. Insgesamt hatte das Programm keine Auswirkungen auf die zentralen Beschäftigungsindikatoren, weder extensiv (Beschäftigung) noch intensiv (Arbeitsstunden, Einkommen). Allerdings führte das Programm (i) zu einer Verschiebung der Beschäftigung hin zu Berufen, in denen die Ausbildung absolviert wurd, (ii) einer teilweisen Verbesserung der Arbeitsplatzqualität (schriftliche Verträge, medizinische Versoorgung) und (iii) einer Verbesserung einer Reihe von Indikatoren der Lebensqualität (psychische Gesundheit, spätere Eheschließungen, Zugang zu Finanzen). Darüber hinaus untersuchen wir die Erwartungen und Wahrnehmungen der politischen Akteure in Bezug auf den Erfolg des Programms. Wir stellen fest, dass die Akteure (i) a priori zu optimistische Vorstellungen über die Auswirkungen des Programms auf die wichtigsten Indikatoren haben und (ii) ihre Vorstellungen nicht gemäß der Bayes'schen-Regel aktualisieren, wenn sie Informationen über die begrenzte Wirksamkeit des Programms erhalten. Diese Ergebnisse weisen auf ein potenzielles Hindernis für eine adaptive Programmgestaltung in der Entwicklungszusammenarbeit hin und könnten das Fortbestehen einiger suboptimaler Arbeitsmarktinterventionen erklären.
Keywords: C93; I21; J08; J24; J28; O12; O15; 330; Vocational training; labor markets; skills; youth; women; impact evaluation; Ghana